Industrial relations - Ratnam, C. S. Venkata (Oxford University Press, 2006)
esigned to meet the needs of MBA students, this textbook discusses theories and the policy framework, and their impact on the relations between labour and management in the manufacturing sector. It also presents an analytical interpretation of labour statistics and data, through caselets, tables, diagrams, and annexures.